Real-time Biomechanical Modeling for Intraoperative Soft Tissue Registration - Suwelack, Stefan (KIT Scientific Publishing, 2015)
Computer assisted surgery systems intraoperatively support the surgeon by providing information on the location of hidden risk and target structures during surgery. However, soft tissue deformations make intraoperative registration (and thus intraoperative navigation) difficult. In this work, a novel, biomechanics based approach for real-time soft tissue registration from sparse intraoperative sensor data such as stereo endoscopic images is presented to overcome this problem.